Mechanical properties of alkali-activated concrete: A state-of-the-art review - Ding, Yao; Dai, Jian-Guo; Shi, Cai-Jun (Construction & building materials, 2016)
•A holistic review of current research on the mechanical properties of AAC is provided.•The AACs reviewed include slag-based, fly ash-based, and fly ash/slag-based types.•Both static and dynamic mechanical properties of AAC are discussed.•The fracture, bond and high-temperature properties of AAC are also addressed.•The slag/fly ash ratio is a very influential factor to the mechanical properties of AAC. Alkali-activated concretes (AACs) are attracting increasing attention due to their potential as alternatives to ordinary Portland cement concrete (OPCC). This paper is a holistic review of current research on the mechanical properties of AAC including research on its compressive strength, tensile strength, elastic modulus, Poisson’s ratio, stress–strain relationship under uniaxial compression, fracture properties, bond mechanism with steel reinforcement, dynamic mechanical properties, and high-temperature performance. Three types of AAC are reviewed: alkali-activated slag, alkali-activated fly ash, and alkali-activated slag-fly ash concretes. The applicability to AAC of design formulas found in codes of practice that were developed to estimate the basic mechanical performances of OPCC is also discussed. It is shown that, in general, AAC exhibits better bond performance with steel reinforcement and better strength performance after exposure to elevated temperatures than OPCC. For the other reviewed mechanical properties, the differences between AAC and OPCC largely depend on the proportions of raw materials in the concrete; specifically, the slag to fly ash ratio may be a very influential factor. As there is a trend to combine slag and fly ash in the production of AAC to achieve normal temperature curing and environmental friendliness, further research is deemed necessary to determine how the slag to fly ash ratio influences the fundamental mechanical properties of AAC and how this affects practical designs.